2022
DOI: 10.3390/biomedicines10010152
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Treatment with Alirocumab, Flow-Dependent Dilatation of the Brachial Artery and Use of Magnetic Resonance Diffusion Tensor Imaging to Evaluate Vascular Structure: An Exploratory Pilot Study

Abstract: Background: Short-term effects of alirocumab on vascular function have hardly been investigated. Moreover, there is a scarce of reliable non-invasive methods to evaluate atherosclerotic changes of the vasculature. The ALIROCKS trial was performed to address these issues using standard ultrasound-based procedures and a completely novel magnetic resonance-based imaging technique. Methods: A total of 24 patients with an indication for treatment with PCSK9 antibodies were recruited. There were 2 visits to the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The decrease of Lp(a) in their study was 7%, which is statistically important (p = 0.002), but not predictive for FMD improvement. On the other hand, treatment with alirocumab for 10 weeks in the ALIROCKS trial showed a nominal amelioration (+41%), but no significant change of flow-dependent dilatation of the brachial artery [47]. The sample size and duration of treatment with PCSK9 inhibitors were similar among the mentioned studies.…”
Section: Endothelial Dysfunctionmentioning
confidence: 73%
“…The decrease of Lp(a) in their study was 7%, which is statistically important (p = 0.002), but not predictive for FMD improvement. On the other hand, treatment with alirocumab for 10 weeks in the ALIROCKS trial showed a nominal amelioration (+41%), but no significant change of flow-dependent dilatation of the brachial artery [47]. The sample size and duration of treatment with PCSK9 inhibitors were similar among the mentioned studies.…”
Section: Endothelial Dysfunctionmentioning
confidence: 73%
“…Inflammation induced by endothelial dysfunction abnormally induces platelet attachment to endothelial cells in the arterial walls ( 100 ), increasing the cardiovascular risk. Even with short-term treatment, the PCSK9 inhibitors, evolocumab and alirocumab, have been found to improve endothelial function ( 101 , 102 ). Damage to the vascular wall by PCSK9 can occur via a variety of mechanisms.…”
Section: Mechanisms Of Pcsk9 In Thrombosis and Haemostasismentioning
confidence: 99%
“…The result was that vascular endothelial growth factors and P-selectin did not alter. Although flow-dependent dilatation was somewhat improved, there were no discernible long-term benefits of PCSK9 inhibitor therapy on vascular function [ 68 ]. A specific analysis of the ODYSSEY Outcomes trial ( n = 18,924 patients with acute coronary syndromes) showed a reduction in major advanced cardiovascular events (MACE).…”
Section: Endothelial Dysfunction Markers and Pcsk9 Inhibitorsmentioning
confidence: 99%